2021
DOI: 10.1097/cce.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chaplain Patient Navigators and Multidisciplinary Family Meetings on Patient Outcomes in the ICU: The Critical Care Collaboration and Communication Project

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Some chaplains worry, therefore, that adopting this term as central to their professional identity will result in an instrumentalization of this discipline toward objectives such as productivity, societal participation, and cost reduction. In a sense, this trend can already be observed in studies that examine the effects of chaplaincy on well-being, (mental) health, and care costs (Alghanim et al 2021;Buelens et al 2023;Kirchoff et al 2021). Molenaar (2016Molenaar ( , 2022 also notes this movement in the professional profile by the VGVZ, where it states that: "Through the systematic and methodical attention to meaning and belief systems, spiritual caregivers contribute to the well-being of people in relation to themselves, others and their environment."…”
Section: Meaning As Instrumental To External Objectivesmentioning
confidence: 83%
See 1 more Smart Citation
“…Some chaplains worry, therefore, that adopting this term as central to their professional identity will result in an instrumentalization of this discipline toward objectives such as productivity, societal participation, and cost reduction. In a sense, this trend can already be observed in studies that examine the effects of chaplaincy on well-being, (mental) health, and care costs (Alghanim et al 2021;Buelens et al 2023;Kirchoff et al 2021). Molenaar (2016Molenaar ( , 2022 also notes this movement in the professional profile by the VGVZ, where it states that: "Through the systematic and methodical attention to meaning and belief systems, spiritual caregivers contribute to the well-being of people in relation to themselves, others and their environment."…”
Section: Meaning As Instrumental To External Objectivesmentioning
confidence: 83%
“…Studies on the relationship between spirituality, spiritual care, emotional well-being, and quality of life consistently show very small effect sizes that rarely reach statistical significance (Buelens et al 2023;Garssen et al 2021;Kirchoff et al 2021). Alghanim et al (2021) even found that introducing chaplains to an intensive care unit (ICU) who facilitated communication, offered support, and organized multidisciplinary family-meetings was associated with longer stays in the hospital and the ICU, and with higher costs compared to a control group that did not work with a chaplain. This does not mean that chaplaincy might not indirectly affect well-being and quality of life.…”
Section: Meaning As Instrumental To External Objectivesmentioning
confidence: 99%
“…She describes chaplains’ work in terms of individual support, rituals and ceremonies, mediating and bridging community, and being present to show how institutional more than personal factors shape what chaplains do (Cadge 2023). Additional typologies of chaplains’ work, some connected to outcomes, further delineate how chaplains spend their time and the influence it can have on patient satisfaction, anxiety, and other individual level measures of recipient well-being (Alghanim et al 2021; Chow et al 2021; Damen et al 2020; Labuschagne et al 2021; Snowden and Telfer 2017; Tan et al 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Detailed studies of IDT collaboration have been conducted in hospice teams, [ 7 , 8 ] but little investigation has been done into the processes and behaviors of non-hospice palliative care teams. There has been some study of multidisciplinary and interdisciplinary support of advance care planning (ACP) and shared decision making (SDM) particularly in the intensive care unit; [ 9 11 ] however, the question of how specialty palliative care interdisciplinary teams support decision making in the hospital remains unanswered.…”
Section: Introductionmentioning
confidence: 99%